Dam Design and Construction in the USSR's North and Siberia (Op't Proektirovaniia I Stroitelstva Gidrotekhnicheskikh Soorujenii v SSSR v Usloviyakh Severa I Siberi) - Domansky,L K; Kudoyarov,L I; Radchenko,V G (1977)
On the basis of major experimental work and with the use of modern methods of calculating temperature regimes in dams, scientifically justified methods of planning hydrotechnical installations have been worked out for the Far North; basic principles have been established for the design of both earth and concrete dams; and engineering procedures have been introduced that make it possible to work year-round on dam construction. The construction of many dams with various heads has yielded a great deal of experience and proved the possibility of successfully erecting dams under the most severe conditions in the Far North of the USSR. (Author) Trans. from Soviet-American Working Seminar Technology of Cooperative Construction in Extreme North Climates (USSR) May 77.